The Role of Evaluation in Developing and Sustaining Community Health Worker Coalitions: The Example of the Michigan Community Health Worker Alliance. Issue 4 (October 2015) - Kieffer, Edith C.; Yankey, Nicholas; Mitchell, Katherine; Allen, Caitlin G.; Janevic, Mary R.; Thomas, Claireta; List, Justin; Palmisano, Gloria; Roman, Lee Anne
Abstract : Community health workers (CHWs) have demonstrated effectiveness in improving health outcomes and addressing health inequities. Statewide CHW coalitions are supporting expansion of the CHW workforce and influencing health policy. Evaluations can play a key role in sustaining coalitions. This article discusses how evaluation has informed the development, processes, and initiatives of the Michigan Community Health Worker Alliance. We highlight the Michigan Community Health Worker Alliance's internal process evaluation, a statewide survey of CHW programs, and other evaluation activities to illustrate how CHW coalitions can use participatory evaluation to develop and reinforce coalition strengths and accomplish mutual goals. Abstract : Supplemental Digital Content is Available in the Text.